Anticoagulant Preferences and Concerns among Venous Thromboembolism Patients - Lutsey, Pamela L.; Horvath, Keith J.; Fullam, Lisa; Moll, Stephan; Rooney, Mary R.; Cushman, Mary; Zakai, Neil A. (Thrombosis and Haemostasis, 2018)
Background Warfarin and direct oral anticoagulants (DOACs) are used for the initial treatment and secondary prevention of venous thromboembolism (VTE), and have similar efficacy. Patient concerns and preferences are important considerations when selecting an anticoagulant, yet these are not well studied.Methods VTE patients (n = 519) were surveyed from online sources (clotconnect.org, stoptheclot.org and National Blood Clot Alliance Facebook followers [n = 495]) and a haematology clinic in Vermont (n = 24).Results Patients were 83% females and on average (±standard deviation [SD]) 45.7 ± 13.1 years; 65% self-reported warfarin as their initial VTE treatment and 35% a DOAC. Proportions reporting being extremely concerned about the following outcomes were as follows: recurrent VTE 33%, major bleeding 21%, moderate bleeding 16% and all-cause death 29%. When asked about oral anticoagulant characteristics, patients strongly preferred anticoagulants that are reversible (53%), and for which blood drug levels can be monitored (30%). Lower proportions agreed with statements that regular blood testing is inconvenient (18%), that they are comfortable using the newest drug versus an established drug (15%) and that it is difficult to change their diet to accommodate their anticoagulant (17%). In multivariable-adjusted models, patients tended to have had as their initial treatment, and to currently be taking, the oral anticoagulant option they personally preferred.Discussion Patients held the greatest concern for recurrent VTE and mortality, regardless of which treatment they were prescribed. Potential weaknesses of warfarin (e.g., dietary restrictions, regular monitoring) were generally not considered onerous, while warfarin's advantages (e.g., ability to monitor) were viewed favourably.
Keywords: venous thrombosis; warfarin; direct oral anticoagulants; patient preferences; patient concerns